How do Confucian schools and Anglo schools differ? A latent profile analysis based on PISA 2015 - Yu Hu (Large-scale Assessments in Education)
Abstract Students in Confucian culture are typically high-achieving on international assessments such as PISA and TIMSS. To explore factors that may explain the high performance of Confucian students, the present study compared the latent subpopulations of school resources and disciplinary climate in two Confucian countries and two Anglo countries. Using Latent Profile Analysis, the results identified the same number of school profiles in the two countries in the two cultures, and these profiles were similar in their levels of disciplinary climate and school resources. The percentage of high-discipline school profiles is about 11.72% higher in Confucian countries than in Anglo countries. In addition, in both cultures, students who attended high-discipline schools were from higher socioeconomic status (SES) families and performed better in science. These results revealed the importance of the disciplinary climate for a school to be effective and provided evidence indicating that Confucian culture has more schools with a positive disciplinary climate.